All sea level is local. (4th May 2018) - Mitrovica, Jerry X.; Hay, Carling; Kopp, Robert; Lickley, Megan
ABSTRACT: When people read about climate change and sea level rise in the average mass-market, general-interest publication, they nearly always see references to "average global sea level rise" – for instance, that the worldwide average sea level rise will be about three feet (or six feet) by the end of this century. But what does that term really mean? And how useful is it for architects, city planners, businesses and local governments planning the latest bridge, highway, airport, seawall, or other infrastructure near the coast? Just how uniformly do the seas rise or fall? What geophysical processes come into play? And what are the consequences for, say, the east and west coasts of the United States, if all the ice melts on the far-away West Antarctic Ice Sheet?